Effects of intermittent fasting diets on plasma concentrations of inflammatory biomarkers: A systematic review and meta-analysis of randomized controlled trials - Wang, Xiaoli; Yang, Qingqing; Liao, Qiumei; Li, Mengdi; Zhang, Pengyu; Santos, Heitor O.; Kord-Varkaneh, Hamed; Abshirini, Maryame (Nutrition (Burbank, Los Angeles County, Calif.), 2020)
Intermittent fasting (IF) and energy-restricted diets (ERDs) have emerged as dietary approaches to decrease inflammatory status; however, there are no consistent results regarding humans. To achieve a comprehensive conclusion, we aimed to conduct a meta-analysis of randomized control trials (RCTs) to evaluate the effects of IF or ERDs on plasma concentrations of inflammatory biomarkers. We systematically searched online medical databases including Web of Sciences, PubMed, SCOPUS, and Google Scholar up to June 2019. Evaluations of effect sizes were described employing in weighted mean difference and 95% confidence intervals from the random-effects model. Eighteen eligible RCTs were included in this meta-analysis. The pooled estimation from the random-effect model showed that IF regimens and ERDs significantly reduced C-reactive protein (CRP) concentrations (WMD: –0.024 mg/dL; 95% CI: –0.044 to –0.005, I2 = 7.0%). Additionally, IF regimens (WMD: –0.029; 95% CI: –0.058 to –0.000, I2 = 17.9%) were more effective in reducing CRP levels than ERDs (WMD: –0.001 mg/dL; 95% CI: –0.037 to 0.034, I2 = 0.0%). Moreover, based on the treatment duration and types of the studies’ population, a greater reduction was observed in overweight and obese individuals (WMD: –0.03 mg/dL; 95% CI: –0.05 to 0.01, I2 = 42.1%), and in treatment duration ≥8 wk (WMD: –0.03 mg/dL; 95% CI: –0.05 to 0.01, I2 = 0.0%) as well. However, IF and ERDs did not significantly reduced tumor necrosis factor-α (WMD: –0.158 pg/mL; P = 0.549, I2 = 98.3) and interleukin-6 (IL-6) concentrations (WMD: –0.541 pg/mL; P = 0.080, I2 = 94.7%). This meta-analysis demonstrated that IF regimens and ERDs may reduce CRP concentrations, particularly in overweight and obese individuals and through a considerable length of intervention (≥2 mo). However, neither dietary model affected the concentrations of tumor necrosis factor-α or interleukin-6. •Fasting and energy-restricted diets significantly reduced concentrations of C-reactive protein.•Fasting regimens more effectively reduced C-reactive protein than energy-restricted diets.•=Fasting and energy restricting diets reduced CRP concentrations mainly in overweight and obese subjects and for ≥8 weeks